Efficacy and safety of TACE-HAIC combined with tyrosine kinase inhibitors and immune checkpoint inhibitors for the patients with BCLC-defined stage B-C HCC - Liu, Bowen; Yin, Linan; Chen, Yuxin; Hou, Xunbo; Li, Yingchen; Liu, Xuesong; Liu, Ruibao (Frontiers in Oncology, 2025)
BackgroundTo evaluate the therapeutic efficacy and safety profile of combining transarterial chemoembolization (TACE) with hepatic arterial infusion chemotherapy (HAIC) combined with tyrosine kinase inhibitors (TKIs) and immune checkpoint inhibitors (ICIs) in patients with hepatocellular carcinoma (HCC) classified as Barcelona Clinic Liver Cancer (BCLC) stage B or C.MethodsThis single-center retrospective analysis included patients with intermediate-to-advanced HCC diagnosed and treated between January 2020 and December 2023. Of 197 eligible patients meeting inclusion criteria, 103 were allocated to the TACE+HAIC+TKI+ICI (T+H+T+I) group and 94 to the HAIC+TKI+ICI (H+T+I) group. Propensity score matching (PSM) was employed to minimize confounding bias, yielding 50 patients per group in the final matched cohorts. Comparative analyses assessed overall survival (OS), progression-free survival (PFS), objective response rate (ORR), and disease control rate (DCR). Primary endpoints were OS and PFS; secondary endpoints included ORR and safety outcomes.ResultAmong the 100 patients included in the analysis, 50 patients received T+H+T+I therapy while the remaining 50 underwent H+T+I treatment, with median follow-up durations of 13.1 months and 14.3 months, respectively. After PSM, the baseline characteristics showed no significant differences between the two groups. The T+H+T+I group demonstrated superior median overall survival (mOS) (20.77 months [95% CI: 11.37-30.16] vs 14.23 months [95% CI: 12.23-16.24]; P=0.019) and longer median progression-free survival (mPFS) (15.43 months [95% CI: 11.85-19.02] vs 10.60 months [95% CI: 7.71-13.49]; P<0.001) as assessed by modified Response Evaluation Criteria in Solid Tumors (mRECIST) version 1.1. The T+H+T+I regimen exhibited superior tumor control outcomes, with an ORR of 54% and DCR of 76%. However, this group also showed increased toxicity profiles, with 14 patients (28%) experiencing grade ≥3 adverse events.ConclusionFor patients with BCLC stage B-C HCC, the T+H+T+I combination therapy demonstrated superior survival benefits, particularly in those with tumor diameter ≥5 cm and presence of portal vein tumor thrombosis (PVTT), while maintaining an acceptable safety profile.